If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = -3 + 2x Solving 1 = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + -2x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + -2x = -3 + 0 1 + -2x = -3 Add '-1' to each side of the equation. 1 + -1 + -2x = -3 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = -3 + -1 -2x = -3 + -1 Combine like terms: -3 + -1 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| -7(4x+7)=-77 | | [x]-10.5=4.3 | | 2(-4h-13)=37*13h | | 3(6z-1)-4(z+5)=7(z+1) | | 4x+12-x-1=1 | | n-31=9 | | t-0.14=28.12 | | -m-3=3m+9 | | 7m+3-4x=-9 | | -4c=9+2c | | 6x+6y=3 | | 6x+3=3x+27 | | 3-w=8w | | -11x=-18-5x | | 3515625*3515625*3515625*3515625*3515625*3515625= | | -1x=165 | | 6+3=x+8 | | 1.83=0.33+p | | j-12.1=7.53 | | 5(3x-2)+12=3(4x+3)+2 | | j-21.1=7.53 | | -4.5=m+1.9 | | 6x^3-61x^2=10x | | m-0.44=-2.74 | | -5x=27+4x | | -604=x+4.3 | | 3x+7y-21=10xy-21 | | 9x-2-20x+5=40 | | 3z+7=11 | | 6x+1=-6x+1 | | n-31.41=76.50 | | 8x+12x=32 |